Blessed are the poor - Condori Cutimbo, Raúl (2010)
This article is a thoughtful exegesis on “The beatitude of the poor” within the social Latin American context, and specifically of Peru. This in sight may worry because of the socio-economic, cultural, and political situation we live in, where the reality of the poor seems to question and thus undermine the relevance of any approximation that is purely “thematic”. The analysis and insights presented herein are not intended to seek a solution to such complex and real problem.The purpose is primarily one of exegetical character: to understand the message of a text written many years ago –in a socio-cultural environment that is very different from ours –but with a content that is still current for its provocative and puzzling nature, considering that no exegesis can bed one without understanding the text with in the reality one lives in.